Becoming Billie Holiday - Weatherford, Carole Boston, 1956-; Cooper, Floyd (Honesdale, Pa. : Wordsong, 2008)
Jazz vocalist Billie Holiday looks back on her early years in this fictional memoir written in verse.
Includes bibliographical references (p. 116).
Book Links (A.L.A.).
Coretta Scott King Award.
School Library Journal starred.
Book Links (A.L.A.), July 2009.
Booklist, October 2008.
Keywords: Holiday, Billie, -- 1915-1959 -- Juvenile fiction; Holiday, Billie, -- 1915-1959 -- Fiction; Holiday, Billie, -- 1915-1959 -- Fiction; African Americans -- Juvenile fiction; African Americans -- Fiction; African Americans -- Fiction